TRANSITIONAL AND TRANSFORMATIONAL SPACES: MENTORING YOUNG ACADEMICS THROUGH WRITING CENTRES - Arlene Hillary Archer; Shabnam Parker (Education as Change, 2016)
The effectiveness of writing centre interventions on student writing in higher education has been well-documented in academic literacies studies. This paper changes the focus of investigation from student to consultant and, consequently, explores the way in which an academic writing centre can function as a mentoring environment for young academics. As a collaborative learning space encouraging transition and transformation, the writing centre is an important site in which postgraduate student consultants are able to explore facets of their academic identities. The role the writing centre plays in the transition from consultant as student to professional is surfaced through a thematic analysis of interview data. We examine the textures of these transitions and the effect writing centre principles have had on teaching practice with particular reference to dealing with English additional language students and the incorporation of an ‘academic development’ perspective into mainstream teaching.